0.12∗
6
1
=
100
12
∗
6
1
=
6∗100
12∗1
=
1∗100
2∗1
=
50
1
=0.02
2.1*\frac{3}{7}=\frac{21}{10}*\frac{3}{7}=\frac{21*3}{10*7}=\frac{3*3}{10*1}=\frac{9}{10}=0.92.1∗
7
3
=
10
21
∗
7
3
=
10∗7
21∗3
=
10∗1
3∗3
=
10
9
=0.9
3\frac{3}{4}*0.4=\frac{3*4+3}{4}*\frac{4}{10}=\frac{15}{4}*\frac{2}{5}=\frac{15*2}{4*5}=\frac{3*1}{2*1}=\frac{3}{2}=1.53
4
3
∗0.4=
4
3∗4+3
∗
10
4
=
4
15
∗
5
2
=
4∗5
15∗2
=
2∗1
3∗1
=
2
3
=1.5
\frac{1}{5}*4.85=\frac{1}{5}*\frac{485}{100}=\frac{1*485}{5*100}=\frac{1*97}{1*100}=\frac{97}{100}=0.97
5
1
∗4.85=
5
1
∗
100
485
=
5∗100
1∗485
=
1∗100
1∗97
=
100
97
=0.97
Объяснение:
y = 5 - (x - 3 )²
y = 5 - (x² - 6x + 9)
y = 5 - x² + 6x - 9
y = -x²+6x-4
Рассмотрим функцию = -x²+6x-4
Функция: квадратичная; График: парабола; a<0 ⇒ ветви направлены вниз
Нули функции:
-x²+6x-4 = 0 | * (-1)
x²-6x+4=0
a= 1; b= -6; c=4
D = b² - 4ac
D = 36 - 16
D = 20
x₁x₂ = -b ± √D / 2a
x₁x₂ = 6 ± √20 / 2
x₁ = 6 - √20 / 2
x₂ = 6 + √20 / 2